INTUITIONISTIC FUZZY IDEALS OF M- â„¾ GROUPS - MALA*, S.K; SHANMUGAPRIYA*, Dr. MM (International Journal of Mathematical Archive, 2018)
In this paper we define and derive lemmas and theorems of Intuitionistic Fuzzy Ideals of M- â„¾ Groups analogous to Fuzzy Ideals.